Thyroid disease in adults - Nystrom, E.; SpringerLink (Online service). (Berlin London Springer, 2011)
This is a comprehensive guide to the assessment and management of adults with thyroid disorders in daily clinical practice. All important aspects and disorders are considered. Relevant information on basic anatomy, embryology, immunology, and physiology is included to provide a better basis for understanding the development of disease and its diagnosis and treatment. Careful attention is given to the important but easily overlooked role of iodine in physiology and thyroid diseases. Currently available biochemical tests and other specific diagnostic tools are also considered in detail. The various common thyroid disorders are then discussed in a series of individual chapters that focus on etiology, pathophysiology, symptomatology, diagnosis, and treatment. Numerous high-quality illustrations and concise fact boxes are included. The authors are all experts with wide experience in three disciplines and a long-standing interest in thyroid disease. The books unique hands-on perspective will make it invaluable for all professionals who deal with thyroid patients.
Anatomy and physiology -- Biochemical investigations -- Other investigations -- Clinical investigation of the thyroid -- Iodine and the thyroid gland in health and sickness -- Autoimmunity and the thyroid gland -- Growth regulation of the thyroid gland -- Thyroiditis, pathogenesis -- Causes of hypothyroidism -- Symptoms of hypothyroidism -- Threatment of hypothyroidism -- Subclinical hypothyroidism -- Myxoedema coma -- Causes of thyrotoxicosis -- Symptoms of thyrotoxicosis -- Treatment options in hyperthyroidism -- Graves disease -- Thyroid-associated ophthalmopathy -- Autonomous adenoma -- Toxic multinodular goitre -- Subclinical thyrotoxicosis -- Thyrotoxicosis in the elderly -- Thyrotoxic crisis/thyroid storm -- Thyroiditis clinical aspects -- Subacute thyroiditis -- Other causes of thyrotoxicosis -- Non-toxic goiter -- Thyroid lumps -- Thyroid cancer -- The thyroid and pregnancy. Thyroid disease in adolescents -- Medicines and other medical preparations and the thyroid -- Thyroid hormone resistance.
Electronic reproduction.
Keywords: Thyroid gland -- Diseases; Thyroid diseases; Thyroid gland -- Physiopathology; Electronic books